Peningkatan Kinerja Karyawan Non-Medis di Rumah Sakit Cimahi Berbasis Motivasi Kerja dan Pembinaan Disiplin - Vasya, Amartha Sheilla; Romi, Mochamad Vrans (Universitas Batanghari, 2024)
Based on performance assessment data for non-medical personnel at Cimahi Hospital, which is still categorized as unsatisfactory, employee performance has dropped due to low work motivation and inadequate discipline training. The purpose of this study is to ascertain how discipline development and work motivation affect non-medical employees' performance at Cimahi Hospital in a partial and simultaneous manner. 33 non- medical staff made up the population of this quantitative study. The complete population was sampled using a saturation sampling methodology, and data were collected via fieldwork and library research before being analyzed using associative and descriptive methods. Utilizing previously processed data, data analysis was performed by examining the SPSS version 26.0 program's output table. The findings of the study indicate that disciplinary development has a partially favorable impact on employee performance, whereas job motivation has no influence at all. Next, the performance of non-medical staff at Cimahi Hospital is concurrently impacted by job motivation and discipline growth.